Makna Sakit: Perspektif Warga Jakarta - Yasinta Astin Sokang (Fakultas Psikologi Universitas Pancasila, 2016)
The common definition of sick is a condition without health. In the other side, sick has various meaning that emphasis on every meaning that given. The meaning of sick as the meaning of health, also influenced by socio-cultural conditions. This research held in Jakarta. The complexity of social and cultural conditions attracted researcher to know the meaning of sick for the citizens of Jakarta. This study used survey methods, by categorizing participant's respond based on the proximity of meaning. The result showed the meaning of sick as physically weakness. Physical condition also combined with other conditions, such as psychological, social relationship, unhealthy lifestyle, and disability. Sick is considered as a disaster, the condition of mortality, and condition of far from God.